2001
DOI: 10.1007/pl00000945
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant expression of perchloric acid-soluble protein reduces cell proliferation

Abstract: Perchloric acid-soluble protein (PSP) may play an important role in the regulation of cellular physiological functions because it has been highly conserved throughout evolution; however, this role has not been well elucidated. In previous reports, we suggested that PSP regulates cell proliferation. In this study, we examined the effect of PSP expression on proliferation of the normal rat kidney cell line NRK-52E, the rat hepatocyte cell line RLN-10, and the rat hepatoma cell line dRLh-84. Cells transfected wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 10 publications
(19 reference statements)
1
16
1
Order By: Relevance
“…Our results did not support this and we found that overexpression of UK114 in HepG2 cells was not able to inhibit cell growth. These results are different from a previous report, in which overexpression of PSP reduced cell proliferation of the normal rat kidney cell line NRK-52E and the rat hepatoma cell line dRLh-84 (22). The reasons for the different results are not clear at present and require further investigation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results did not support this and we found that overexpression of UK114 in HepG2 cells was not able to inhibit cell growth. These results are different from a previous report, in which overexpression of PSP reduced cell proliferation of the normal rat kidney cell line NRK-52E and the rat hepatoma cell line dRLh-84 (22). The reasons for the different results are not clear at present and require further investigation.…”
Section: Discussioncontrasting
confidence: 99%
“…Biological studies of its function suggest that it may play a role in cellular differentiation and development because levels are significantly increased during differentiation from human monocytes to macrophages (17) and during the development process of rat kidney, rat brain, pig liver, and chick liver (11,(18)(19)(20). Furthermore, expression of PSP depends on the proliferation states of the cell and overexpression of PSP reduces cell proliferation of normal rat kidney epithelial NRK-52E cells (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…For example, UK was reported to inhibit protein synthesis in vitro in rabbit reticulocyte lysate (35). Overexpression of UK suppressed cell proliferation of normal rat kidney epithelial cells without any influence on cell viability (20). In addition, UK was reported to act as an endoribonuclease that inhibits translation by cleaving mRNA (35).…”
Section: Discussionmentioning
confidence: 99%
“…1) We have reported that PSP is related to cell proliferation and/or differentiation. [2][3][4][5] In fetal rat kidney, PSP was expressed in differentiated renal tubules but not in glomeruli. 2) In cultured cell lines, the expression of PSP was lower during the proliferation phase than during the confluent phase.…”
mentioning
confidence: 99%
“…4) Overexpression of PSP inhibited cell proliferation in cultured cell lines. 5) In chick embryos, PSP is expressed in the neuroepithelial cells at embryonic day 3. When the function of PSP in the neuroepithelial cells of chick embryos was neutralized by anti-PSP immunoglobulin G (IgG), the neuroepithelial cells formed a wavy line due to excess-cell proliferation, which was detected by counting the proliferating cell nuclear antigen (PCNA) positive cells.…”
mentioning
confidence: 99%